Nano-biochar in soil ecosystems: Occurrence, transport, and negative environmental risks - Feiying Zhang (Ecotoxicology and Environmental Safety)
Nano-biochar (nano-BC) in the soil environment has begun to attract great attention owing to its better dispersion and stronger migration ability than bulk-biochar (bulk-BC) for soil remediation. Here we review the behaviors of nano-BC during sorption and transit in soil ecosystems as well as the consequences of nano-BC that have been observed. The ability of nano-BC to absorb organic and heavy metal contaminants are well-established, and this feature may significantly affect the distribution of these pollutants within the soil matrix. Beyond its potential to exert adverse ecotoxicological impacts on soil fauna, nano-BC also alters the soil’s microbial and enzymatic activities, plant growth, and physicochemical properties. The vertical and horizontal transport of nano-BC may be facilitated by soil flora. Pollutants associated with nano-BC may disperse further in soil as a result of its movement. Prior to the widespread application of nano-BC in soil ecosystems, future research should focus on assessing the environmental risks associated with the unforeseen negative effects of nano-BC on human health and plant life.